(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The inadequate realization of the textile production target despite the increase in textile production has an impact on the sales that will be obtained by the company. Employee performance continues to decline due to the lack of motivation in employees and the compensation given is considered incompatible with the work that the employee produces or in other words, the compensation obtained is below the UMR. This study aims to determine how the influence of work motivation and compensation on employee performance at PT. A. The research method used is descriptive-verification method. The sample used in this study were 67 employees who worked as a production division at PT.A. Data processing was performed using multiple linear regression, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Based on the research results it can be concluded that there is an influence between work motivation on employee performance at PT. A and there is an influence between compensation on employee performance at PT. A and there is a simultaneous influence between work motivation and compensation on employee performance at PT. A